1993
DOI: 10.1080/02772249109357905
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation and effect of chlorophenoxy herbicide on plant pigments and carbohydrates of sunflower (Helianthus annuusL.)

Abstract: The dissipation pattern of the chlorophenoxy herbicides (2,4-D and 2,4,5-T) residues in sunflower plants (Helianthus annuus L.) has been studied along with its effect on the changes of plant pigments (chlorophyll-a,b, total chlorophyll, carotene and anthocyanin), sugar and starch in different parts of the plant. The residues of 2,4-D and 2,4,5-T remained for larger period of time (10 days) at higher concentrations than the lower concentration. The concentrations of chlorophylls and carotene were found to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Thus, the changes in the reflectance indices we measured in the greenhouse are likely to persist longer than our experiment. We observed the common sub-lethal responses among plants exposed to herbicides (Doong et al 1993;Koley et al 1993): a reduction in chlorophyll (NDVI, Red Edge) and carotenoid content (ΔPRI). ARI, which provides a measure of anthocyanin concentration corrected for chlorophyll absorbance, may prove to be a particularly sensitive indicator, based on the consistency between laboratory and the field results (Figs.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, the changes in the reflectance indices we measured in the greenhouse are likely to persist longer than our experiment. We observed the common sub-lethal responses among plants exposed to herbicides (Doong et al 1993;Koley et al 1993): a reduction in chlorophyll (NDVI, Red Edge) and carotenoid content (ΔPRI). ARI, which provides a measure of anthocyanin concentration corrected for chlorophyll absorbance, may prove to be a particularly sensitive indicator, based on the consistency between laboratory and the field results (Figs.…”
Section: Discussionmentioning
confidence: 89%
“…The spraying of 2,4-D dimethyl amine herbicide (selective) will affect the physiological and biochemical processes of the main plants. [10] reported spraying herbicide 2,4-D up to 1,000 ppm significantly inhibited leaf chlorophyll (a, b, total), carotenoids, and carbohydrate content of sunflower plants at 2, 6, and 10 days after spraying (DAS). [11] found that different herbicide treatments significantly affected the SPAD total chlorophyll in lowland rice at 70 DAS.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al, (2006) have reported that the chlorophyll content decreased consistently with increased rates of two herbicides in chickpeas, together with nitrogenase activity and seed production. Also, Koley et al, (1993) have demonstrated that two chlorophenoxy herbicides (2,4-D and 2, 4, 5-T) reduced the chlorophyll content in sunflower (Helianthus annuusL. ).…”
Section: Introductionmentioning
confidence: 99%